Response of cassava cultivars to African cassava mosaic virus infection across a range of inoculum doses and plant ages - Houngue, J.A.; Pita, J.S.; Ngalle, H.B.; Zandjanakou-Tachin, Martine; Fotso Kaute, A.; Cacaï, G.H.T.; Bell, J.M.; Ahanhanzo, C. (Public Library of Science, 2019)
Cassava production in Africa is constrained by cassava mosaic disease (CMD) that is caused by the Cassava mosaic virus (CMV). The aim of this study was to evaluate the responses of a range of commonly cultivated West African cassava cultivars to varying inoculum doses of African cassava mosaic virus (ACMV). We grafted 10 cultivars of cassava plants with different inoculum doses of CMV (namely two, four, or six CMD-infected buds) when the experimental plants were 8, 10, or 12 weeks old, using non-inoculated plants as controls. Three cultivars showed disease symptoms when grafted with two buds, and four cultivars showed disease symptoms when grafted with four or six buds. Most cultivars became symptomatic six weeks after inoculation, but one (‘TMS92/0326’) was symptomatic two weeks after inoculation, and two (‘Ntollo’ and ‘Excel’) were symptomatic after four weeks. Root weight tended to be lower in the six-bud than in the two-bud dose, and disease severity varied with plant age at inoculation. These results indicate that the level of CMD resistance in cassava cultivars varies with inoculum dose and timing of infection. This will allow appropriate cultivars to be deployed in each production zone of Africa in accordance with the prevalence of CMD.